Pengaruh Pemahaman Materi Aqidah Akhlak terhadap Peningkatan Kepedulian Sosial Siswa Kelas VII MTs Alam Al Hafidz Baiturrahman Bontang - Karina, Karina; Hamdani, Hamdani (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
The belief system (Aqidah) and ethics (Akhlak) are guidelines that demand good behavior from Muslims, in their daily lives as well as in specific behaviors. This is very important so that the future generations of Muslims can have good conduct. Concern or social attitudes are actions, not just thoughts or feelings. Showing concern is not just about knowing what is right or wrong, but also having the willingness to take even the smallest actions. This research aims to determine whether the understanding of Aqidah Akhlak material affects the improvement of students' social concern. The data collection methods used include interviews, observations, questionnaires, and the SPSS application. The collected data will be analyzed using descriptive analysis techniques. The research population consists of all 38 seventh-grade students at MTs Alam Al Hafidz Baiturrahman. From the percentage calculation of the Questionnaire Variables (X) Aqidah Akhlak and variable (Y) students' social concern, it can be concluded that the students' understanding of Aqidah Akhlak material falls within the interval class of 50-24, with 16 respondents being high (42.10%), 21 respondents being moderate (55.26%), and 1 respondent being low (2.63%). Thus, the students' understanding of Aqidah Akhlak material is moderate at 55.26%. The students' social concern falls within the interval class of 47-22, with 19 respondents being high (50%), 11 respondents being moderate (28.94%), and 8 respondents being low (21.05%). Therefore, the social concern of the seventh-grade students is classified as high at 50%. The research results show an increase in students' social concern as evidenced by the Hypothesis Test results, which indicate that the calculated value (r) is greater than the table value (0.463-0.320). Thus, the understanding of Aqidah Akhlak material can significantly influence students. Therefore, the understanding of Aqidah Akhlak material can be applied to the entire student population at MTs Alam Al Hafidz Baiturrahman Bontang.